On One Chronological Question of Early Croatian Archaeology (asked by Ljubo Karaman) (Archaeologia Adriatica, 2010)
Referring to the hypothesis about the appearance of three-beaded earrings in Croatia only in the late period of the Middle Ages, which Stjepan Gunjača based on the hoard find of three-beaded earrings and coins of the Angevin king Louis I (1342-1382) in a closed grave unit found during excavations of the cemetery surrounding the ruined church of St. Michael at Brnaze near Sinj, Ljubo Karaman in his article "Two chronological questions of Early Croatian archaeology" in the first section on "The period of appearance three beaded earrings of the socalled Kiev type in Dalmatian Croatia" first questioned and then rejected Gunjača’s claim. As the main argument for confirmation of his opinion about the appearance of the three beaded earrings in the early medieval period, he presented a photograph from the archives of the Museum of Croatian Antiquities, where the grave unit included spurs of the Carolingian type that he dated to the 9th century, along with a three-beaded earring decorated with filigree. Faced with Karaman’s argument, for which he had no proper answer, Gunjača did not further enter into discussions about the chronology of these earrings. Although more than fifty years have passed since then, in which the science of archaeology has greatly evolved through new findings, the fact remains that numerous art historians and archaeologists involved in the typology and chronology of the Middle Ages of Croatia ignore this opinion of Karaman. In fact, they avoid mentioning this article by Karaman and the arguments set forth in it as if it had never even been written. However, until the dilemma presented by Karaman is not solved, all conjectures about the chronology of this type of jewelry are scientifically defective and inconsistent. The author of this contribution, dedicated to the meritorious archaeologist and professor J. Belošević, solves the problem of Karaman’s hypothesis, by discovering that the three-beaded earring should be removed from the grave unit on the archival photograph, as it was placed there by chance. In this manner a serious problem in archaeological science has been removed and a more justified dating of medieval three-beaded earrings is made possible.
Keywords: three-beaded earrings; medieval period; Carolingians; spurs; grave